2020
DOI: 10.1101/2020.07.08.193045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-dose live-attenuated YF17D-vectored SARS-CoV2 vaccine candidate

Abstract: AbstractThe explosively expanding COVID-19 pandemic urges the development of safe, efficacious and fast-acting vaccines to quench the unrestrained spread of SARS-CoV-2. Several promising vaccine platforms, developed in recent years, are leveraged for a rapid emergency response to COVID-191. We employed the live-attenuated yellow fever 17D (YF17D) vaccine as a vector to express the prefusion form of the SARS-CoV-2 Spike antigen. In mice, the vaccine candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…The neutralizing antibody levels rose significantly after the booster vaccination reaching a PRNT80 geometric mean titer (GMT) of 207 and PRNT50 GMT of 761 that are comparable or exceeding titers of other DNA vaccines evaluated in nonhuman primates 13 and mice 18 . The PRNT50=761 is similar to the 50% titers elicited in hamsters vaccinated with single-dose, live-virus vectored vaccines: Ad26-vectored vaccine PsVNA50 <1000; VSV-vectored vaccine PRNT50 <1000, and Yellow Fever-vectored vaccine PRNT50 <1000 [7][8][9] . Neutralization titer was plotted against viral RNA detected in lung tissue collected at the time of euthanasia.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The neutralizing antibody levels rose significantly after the booster vaccination reaching a PRNT80 geometric mean titer (GMT) of 207 and PRNT50 GMT of 761 that are comparable or exceeding titers of other DNA vaccines evaluated in nonhuman primates 13 and mice 18 . The PRNT50=761 is similar to the 50% titers elicited in hamsters vaccinated with single-dose, live-virus vectored vaccines: Ad26-vectored vaccine PsVNA50 <1000; VSV-vectored vaccine PRNT50 <1000, and Yellow Fever-vectored vaccine PRNT50 <1000 [7][8][9] . Neutralization titer was plotted against viral RNA detected in lung tissue collected at the time of euthanasia.…”
Section: Discussionsupporting
confidence: 52%
“…Histopathology includes areas of lung consolidation, followed by pneumocyte hyperplasia as the virus is cleared. At least three candidate vaccines have been tested for efficacy in the Syrian hamster model [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological analysis of infected hamsters shows multifocal interstitial pneumonia characterized by pulmonary consolidation starting as early as 2 dpi. Inflammation is associated with leukocyte infiltration, comprised primarily of macrophages and neutrophils, and an increase in type I and III interferon (IFN) and other pro-inflammatory cytokine and chemokines [14, 15]. High-resolution computed tomography scans shows airway dilation and consolidation in the lungs of infected hamsters [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two of the influenza-based candidates are designed for intranasal administration. A live attenuated yellow fever vector-based vaccine (YFS0) expressing the prefusion form of the S protein recently showed that a single dose protected most hamsters in a SARS-CoV-2 challenge model ( 109 ).…”
Section: Different Vaccine Approaches Used In Covid-19 Vaccine Develomentioning
confidence: 99%